Antibacterial activity of green tea (Camellia sinensis) extracts against various bacteria isolated from environmental sources - Kumar, Amit; Kumar, Ajay; Thakur, Payal; Patil, Sandip; Payal, Chandani; Kumar, Anil; Sharma, Pooja (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> Tea is cultivated in many countries of the world. India is largest tea (black tea) producer in world followed by Japan (green tea) and China. In the present study Camellia assamica (Green tea) leaves extracts were tested for antibacterial activity against various bacteria isolated from environmental sources. Different bacteria were isolated from sewage samples collected from different places at Solan Himachal Pradesh. Isolated bacteria were identified by Gram staining and biochemical tests. A total of six bacteria were identified at Department of Microbiology at SILB Solan (H.P) Green tea leaves extracts were tested for antibacterial activity. Tea leaves were collected from Palampur, Himachal Pradesh. Three different extracts were prepared by using standardized protocols. All the extracts were tested for antibacterial activity by disc diffusion method. Antibacterial assay was performed at 10µl, 20µl, and 30µl concentrations. Significant antibacterial activity was reported for all extracts with results. Aqueous extracts has shown little antibacterial activity against six bacteria isolated. Maximum antibacterial activity was found in methanolic extracts. Our study reflects the chemotherapeutic use of green tea.